2016
DOI: 10.3109/10641963.2015.1131290
|View full text |Cite
|
Sign up to set email alerts
|

Effect of spironolactone on patients with resistant hypertension and obstructive sleep apnea

Abstract: Spironolactone reduced the severity of OSA and reduced blood pressure in resistant hypertension patients with moderate-to-severe OSA. These findings may assist in the treatment of OSA in patients with resistant hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 23 publications
2
46
1
3
Order By: Relevance
“…The follow-up was 12 weeks. AHI decreased significantly in the treatment group but not in the control group [28].…”
Section: Impact Of Mineralocorticoid Receptor Antagonists On Osa Sevementioning
confidence: 68%
See 1 more Smart Citation
“…The follow-up was 12 weeks. AHI decreased significantly in the treatment group but not in the control group [28].…”
Section: Impact Of Mineralocorticoid Receptor Antagonists On Osa Sevementioning
confidence: 68%
“…Moreover, except one study, all studies followed non-randomized, observational design. Secondly, it is difficult to judge if the effect of treatment with aldosterone antagonists was related to combatting the deleterious effects of aldosterone or to the decrease and changes in distribution of extracellular fluid during sleep by the diuretic effects of the drugs [26][27][28][29].…”
Section: Impact Of Mineralocorticoid Receptor Antagonists On Osa Sevementioning
confidence: 99%
“…One of the explanations for the high occurrence of OSA in CKD patients is sodium and water retention mediated by abnormal renin-angiotensin-aldosterone system (RAAS) activity [42]. In patients with OSA, an abnormal diurnal RAAS activity has been reported [43], and one study has shown, that both OSA severity and BP levels were reduced when adding aldosterone antagonists to the antihypertensive treatment in hypertensive OSA patients [44]. Hence, when analysing the effect of CPAP treatment, it is relevant to evaluate eventual changes in vasoactive hor-Open Journal of Nephrology mones and renal handling of sodium and water as an explanation for BP response.…”
Section: Discussionmentioning
confidence: 99%
“…1), and 6-beta-hydroxy-7-alpha-methylthiospironolactone as the main ones [2]. Spironolactone has been widely used for decades and its side effects have been studied and documented [38], but despite being used also in children, the dosing recommendations are based on clinical trials performed in the adult population and/or expert opinion and clinical experience. As such, studies evaluating the pharmacokinetic profile of spironolactone in pediatric age groups contribute to the refinement of evidence-based dosing recommendations in children.
Fig.
…”
Section: Introductionmentioning
confidence: 99%